In Dairy Cows with Clinical Mastitis Do Systemic Antimicrobials in Addition to Intramammary Antimicrobials Improve Clinical Cure Rates Compared to Intramammary Antimicrobials Only? - Barden, Matthew (Veterinary Evidence, 2016)
Clinical bottom line In spite of limitations to the available studies, in cattle with clinical mastitis and an absence of systemic signs there is no evidence that combined systemic and intramammary antimicrobial therapy improves clinical cure rates compared to intramammary antimicrobial therapy only. In two studies, cattle with severe coliform mastitis showed improved clinical parameters following combined systemic and intramammary antimicrobial therapy compared to intramammary antimicrobial therapy only.